2018
DOI: 10.1016/j.cgh.2018.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Rare Sucrase-isomaltase Pathogenic Variants in Irritable Bowel Syndrome Patients

Abstract: Patients with irritable bowel syndrome (IBS) often associate their symptoms to certain foods. In congenital sucrase-isomaltase deficiency (CSID), recessive mutations in the SI gene (coding for the disaccharidase digesting sucrose and 60% of dietary starch) cause clinical features of IBS through colonic accumulation of undigested carbohydrates, triggering bowel symptoms. Hence, in a previous study, we hypothesized that CSID variants reducing SI enzymatic activity may contribute to development of IBS symptoms. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 8 publications
1
77
1
2
Order By: Relevance
“…This is vital as, despite available evidence, many pediatric gastroenterologists do not test for these deficiencies 5 . Less invasive studies, such as genetic testing and breath testing 44,45,48,49 , may encourage physicians to consider testing for disaccharidase deficiency as part of the workup for pediatric IBS when indicated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is vital as, despite available evidence, many pediatric gastroenterologists do not test for these deficiencies 5 . Less invasive studies, such as genetic testing and breath testing 44,45,48,49 , may encourage physicians to consider testing for disaccharidase deficiency as part of the workup for pediatric IBS when indicated.…”
Section: Resultsmentioning
confidence: 99%
“…Heterozygous carriers of the CSID mutation had an almost 2-fold increased risk of IBS (p = 0.074; odds ratio = 1.84) 43 . In a genotype study of 2207 IBS patients, Garcia-Etxebarria et al (2018) found that when compared with matched reference population from exome aggregation consortium, most SI rare pathogenic variants were identified in IBS patients and further analysis showed these variants increased the risk of IBS 45 . Table 2 outlines the studies referred to in this review that found a link between disaccharidase deficiencies and IBS.…”
Section: Prevalence Of Disaccharidase Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…43,44 When symptoms of bloating, gas, and diarrhea are present and not fully managed by medical and nutrition therapies for IBS, sucrase-isomaltase deficiency (SID) should be considered. 45,46 Genetic mutations in the SI gene affects sucrose and disaccharide digestion in congenital SID or SID when found in adulthood and may cause symptoms similar to IBS. 46 Diagnosis of SID may be made through symptom development with sucrose ingestion, a carbon 13 ( 13 C-sucrose) breath test, or endoscopic biopsy.…”
Section: Other Considerationsmentioning
confidence: 99%
“…45,46 Genetic mutations in the SI gene affects sucrose and disaccharide digestion in congenital SID or SID when found in adulthood and may cause symptoms similar to IBS. 46 Diagnosis of SID may be made through symptom development with sucrose ingestion, a carbon 13 ( 13 C-sucrose) breath test, or endoscopic biopsy. In this case, the breath test has been shown to be accurate and does not cause symptoms as would occur with actual sucrose ingestion.…”
Section: Other Considerationsmentioning
confidence: 99%